Emotion regulation and mental health in young elite athletes - Regborn, F, F.; Holmström, S.; Svensson, M.; Sjögren, M. (Sports, 2025)
Emotion regulation strategies, specifically expressive suppression (ES) and cognitive reappraisal (CR), are known to influence mental health outcomes in the general population and adult elite athletes. Young elite athletes, who face unique academic and athletic pressures, remain understudied in this regard. The main aim of this study was to examine the relationship between ES and CR and mental health in young elite athletes. This longitudinal study included 93 young elite athletes (aged 15-17) attending upper secondary education in Sweden. Participants completed the Emotion Regulation Questionnaire and the General Health Questionnaire at three time points over 12 months. Linear mixed models were used to examine associations between ES, CR, and mental health. Higher use of ES was significantly associated with poorer mental health (ß = 0.34, p < 0.001), while greater use of CR predicted better mental health (ß = -0.33, p < 0.001) across the study period. Expressive suppression and CR are both important for the mental health of young elite athletes, with CR being protective and ES conferring risk. Given the observed associations, future research could examine whether interventions aiming to enhance CR and reduce ES are linked to better mental health in young elite athletes.